Keller/eGFR ratio as a simple and useful tool to make a first differentiation between renal aging and chronic nephropathy in large populations (2025)
Background Chronic kidney disease (CKD) prevalence increases with age, but distinguishing physiological renal ageing from pathological CKD remains a major diagnostic challenge. Current CKD definitions based solely on estimated glomerular filtration rate (eGFR) often lead to overdiagnosis in elderly individuals with normal age-related decline. This study explores the use of the Keller/eGFR ratio as a simple and useful tool to differentiate normal renal ageing from true nephropathy in large populations. Methods Keller formula (GFR = 130—age) was applied to model the expected physiological GFR decline across the lifespan. The ratio between Keller-derived GFR and measured eGFR (CKD-EPI) was analyzed to distinguish physiological ageing (Keller/eGFR ≤ 1) from pathological decline (Keller/eGFR > 1). The approach was compared with classical biochemical, urinary, and imaging markers and validated using data from the Abruzzo cohort of older adults. Results Keller/eGFR ratio provided a clear separation between individuals with expected age-related GFR reduction and those with evidence of underlying CKD. In patients with Keller/eGFR ≤ 1, biochemical parameters (creatinine, urea, hemoglobin, calcium–phosphorus metabolism) and urinalysis remained within normal limits, and imaging findings were unremarkable. Conversely, Keller/eGFR > 1 was associated with typical CKD features, including anemia, mineral abnormalities, and structural renal alterations. Integrating this ratio with clinical and laboratory data significantly reduced CKD overdiagnosis in elderly subjects. Conclusions The Keller/eGFR ratio represents a practical, low-cost, and easily applicable index for the first-line screening of kidney function in older adults. When combined with biochemical and imaging markers, it enhances diagnostic accuracy and helps avoid excessive medicalization related to CKD misclassification. Wider implementation in population studies could improve epidemiological stratification and resource allocation in nephrology care.